2018
DOI: 10.1111/ijd.14032
|View full text |Cite
|
Sign up to set email alerts
|

Stress and psoriasis

Abstract: The links between psoriasis and stress are complex. This article proposes a review of the literature on the relationship between stress and psoriasis. In 31-88% of cases, patients report stress as being a trigger for their psoriasis. There was also a reported higher incidence of psoriasis in subjects who had a stressful event the previous year, suggesting that stress may have a role in triggering the disease in predisposed individuals. Stress is also a consequence of psoriasis outbreaks. Understanding the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 126 publications
2
74
0
2
Order By: Relevance
“…It is estimated that 31% to 88% of patients report stress as a trigger for their psoriasis. 24,25 In our patients, 40.3% reported that stress was a precipitating factor. This percentage is comparable to that in data from China (34.5%) and Malaysia (48.3%) but is much lower than that reported in Maghreb (79.4%).…”
Section: Discussionmentioning
confidence: 53%
“…It is estimated that 31% to 88% of patients report stress as a trigger for their psoriasis. 24,25 In our patients, 40.3% reported that stress was a precipitating factor. This percentage is comparable to that in data from China (34.5%) and Malaysia (48.3%) but is much lower than that reported in Maghreb (79.4%).…”
Section: Discussionmentioning
confidence: 53%
“…Among patients with moderate‐to‐severe psoriasis who took part in a study by Gupta et al ., 20 26% reported that they had experienced at least one episode in a month where ‘people made a conscious effort not to touch them’ as a result of the visible presence of psoriasis. Furthermore, stress has been shown to be a trigger for both psoriasis onset and exacerbation 21 . In one study, 88% of patients linked psychologic stress to exacerbation of their disease and 68% of patients reported that they had experienced a psychologically stressful life event in the 3 months prior to the onset of psoriasis 22 …”
Section: Discussionmentioning
confidence: 99%
“…The authors postulated that stress contributed significantly 7 to disease impact and, in fact, even greater than the visibility of disease itself. 7 Furthermore, the stress resulting from perceived stigma may be a trigger for psoriasis exacerbation, 36 and the relationship between stigma and psoriasis flares can become a vicious, perpetual cycle, highlighting the pervasiveness of stigma. Indeed, in studies of weight stigma, anticipated stigma, particularly, has been shown increase markers of cardiovascular reactivity (ie, higher blood pressure) and therefore contribute to cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%